Differential games approach to trade with exhaustible resources - Phemelo Tamasiga; Anton Bondarev (University of Basel, Center of Business and Economics (WWZ), 2014)
The paper presents a model of world economy with two countries where one of them dubbed home sells the exhaustible resource to final producers in both countries, which compete at the final goods market. The interaction between final producers is reached via the sticky price mechanics, whereas price continuously adjusts to produced final product quantities. Production technology in both countries includes the resource as an essential input plus the variety of intermediate products. We demonstrate how opening up to trade of the exhaustible resource may be beneficial for the home economy by promoting technical change and capital accumulation via increased resource rents and relative factor prices movements. This leads to the increase in social welfare due to taste for variety and fosters structural change in the home country.
Keywords: F1; L16; Q37; C6; C7; 330; structural change; resource economics; international trade; differential games